Clusters industriais e performance regional: contribuições à teoria da vantagem competitiva sustentável - Figueiredo, Jeovan de Carvalho (2009)
This study provides evidence regarding the strategic dynamics of competitive clusters. It’s suggested that the competitiveness must be pursued not only by the increasing of economic profits, but it also must generate benefits for the local society and the country. This is necessary to understand better the whole effects of the clusters for the set of organizations who act jointly in the same region. This work aims to determine which are the effects of clusters in the region where they are established. A strategy of research of multiple stages was adopted, having involved initially an exploratory research, in a cluster of information and communication technology. The results had been used in the refinement of hypotheses for a quantitative research, in which 645 observations had been analyzed, correspondent to the cities of the state of São Paulo. The results suggest that the industrial clusters cities are those who present superior performance of exporting intensity and aggregation of value. These cities still present high levels of wealth for the townspeople, and the cities with industrial clusters, also have bigger longevity of the citizens. But any evidence of that cities with clusters are related to the biggest years of study was found. An interesting evidence is related to the environmental problems. The group of cities with clusters presented more related ambient alterations. Thus, a necessary revision of the model of competitive advantage in clusters is suggested in this work, contemplating the contemporary questions about environmental problems.